Biomechanical parameters of swings on rings - Serfain, R.; Golema, M.; Siemienski, A. (Sporto Mokslas-Sport Science, 2005)
To describe the overloading of gymnasts` motor system during execution of maximal swings on rings, we investigated a junior gymnast of class I, 14 years of age, with body mass 53.1 kg and body height 1.61 m. The athlete carried out a series of ten maximal swings between consecutive natural hangs. Kinematics of the gymnast`s centre of mass (COM) and reaction forces in cables were measured and synchronized in the SIMI Motion system. We found two motor phases in the signatures of the reaction forces in cables: with support and without support. During the phase without support the potential parameters of swings are acquired: the range and momentum of the COM. Those parameters did not differentiate significantly the kinematics of the COM between forward and backward swings. Changes in the vertical velocity were symmetrical during the sways in both directions. The horizontal velocity can be, however, of importance for the technique of swing execution. Overloading acts on the gymnast`s body during the phase with support which arises at the "bottom" of each swing. The overloading magnitude depends on the value of force and the time of its duration. Maximal reaction forces in cables were equal to 5.5 to 6.5 BW, and the time of their rapid increase was 0.12 s on average. Those forces during the phase without support differentiated between forward and backward swings in terms of their maximal values and the rate of increase. Maximal vertical acceleration during this phase amounted to 30 m/s2. It is important to mention that swinging on rings has advantageous movement parameters due to horizontal oscillations of the COM. The theoretical model of this exercise without consideration of horizontal oscillations predicts the maximal values of overloading at 12.5 and 10.5 BW in backward and forward swings, respectively.